Answer: question,
" The sum of two numbers is 17"
x + y = 17 --------(1)
y = 17 - x
Second statement is " Their product is 70 "
xy = 70-----(2)
Now we replace the value of y from the equation (1) to equation (2).
(17 - x)x = 70
17x - x² = 70
x² - 17x + 70 = 0
x² - 10x - 7x + 70 = 0
x(x - 10) - 7(x - 10) = 0
(x - 10)(x - 7) = 0
x - 10 = 0
x = 10
and (x - 7) = 0
x = 7
Now we put the values of x in equation 1.
For x = 10,
y = 17 - 10
y = 7
For x = 7
y = 17 - 7
y = 10
Therefore, two numbers are 10 and 7.
Step-by-step explanation:
10 and 7